2014
DOI: 10.1007/s13213-014-0840-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microbial communities in heavy crude oil from Saudi Arabia

Abstract: The complete mineralization of crude oil into carbon dioxide, water, inorganic compounds and cellular constituents can be carried out as part of a bioremediation strategy. This involves the transformation of complex organic contaminants into simpler organic compounds by microbial communities, mainly bacteria. A crude oil sample and an oil sludge sample were obtained from Saudi ARAMCO Oil Company and investigated to identify the microbial communities present using PCR-based culture-independent techniques. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…Proteocatella has been detected in penguin guano (92), in the canine oral microbiome (93), and in dairy wastewater storage ponds (94). Veillonellaceae, which is closley related to Clostridium, has been found in a variety of habitats ranging from the human oral microbiome (95) to crude oil (96). Thus, the bacterial communities reported in this study represent taxa that can be commonly found in aquatic habitats and those associated with common vertebrate species used in human food production.…”
Section: Discussionmentioning
confidence: 69%
“…Proteocatella has been detected in penguin guano (92), in the canine oral microbiome (93), and in dairy wastewater storage ponds (94). Veillonellaceae, which is closley related to Clostridium, has been found in a variety of habitats ranging from the human oral microbiome (95) to crude oil (96). Thus, the bacterial communities reported in this study represent taxa that can be commonly found in aquatic habitats and those associated with common vertebrate species used in human food production.…”
Section: Discussionmentioning
confidence: 69%
“…The persistence of the Firmicutes group after biostimulation with SG indicates that this group constitutes a stable and vital component of the bacterial community structure of the desert soil. Sequences in this group are prevailed by Bacillus, Salirhabdus and Virgibacillus , which are known to have oil-degrading species ( Kothari et al, 2013 ; Borah and Yadav, 2014 ; Roy et al, 2014 ; Albokari et al, 2015 ). The detection of sequences belonging to the class Chloroflexi only in the treatment with SG and not in others, strongly suggests that these bacteria have been growing in the sludge and brought into the soil.…”
Section: Discussionmentioning
confidence: 99%
“…in the microbial community in heavy crude oil sludge was reported in Saudi Arabia, Oman, and Nigeria. [ 41 43 ]. Bacillus and Paenibacillus sp.…”
Section: Discussionmentioning
confidence: 99%